A randomized controlled trial of Velcro versus standard twill ties following pediatric tracheotomy. (7th May 2017) - Hart, Catherine K.; Tawfik, Kareem O.; Meinzen‐Derr, Jareen; Prosser, John Drew; Brumbaugh, Cheryl; Myer, Amy; Ward, Jonette A.; de Alarcon, Alessandro
Abstract : Objectives/Hypothesis: Tracheotomy is a common procedure. A reliable method of securing the tracheotomy tube is essential to minimize accidental decannulation. However, skin breakdown has been reported in ∼30% of patients. We sought to evaluate rates of skin‐related complications and accidental decannulation with the use of Velcro ties compared to twill ties. Study Design: A nonblinded, randomized controlled trial comparing Velcro versus twill ties in patients undergoing tracheotomy between July 1, 2014 and January 31, 2016. Methods: Patients ≤21 years of age were recruited and randomized to receive either Velcro or twill ties. The primary outcome measure was skin‐related complications. The secondary outcome measure was accidental decannulation. Outcome measures were followed through postoperative day 5. Results: Ninety‐three patients were eligible, and 63 were enrolled. No patients were withdrawn. Fifty‐seven patients were included in the analysis. Twenty‐seven (47.4%) received Velcro, and 30 (52.6%) received twill. Five enrolled patients did not undergo tracheotomy (one Velcro, four twill). One was diagnosed with a genetic skin condition after enrollment but prior to undergoing tracheotomy. Patient characteristics were similar between groups. No significant differences were found with respect to skin‐related complications ( P = .59). Six patients (20%) with twill ties required early tie change compared to two (7.4%) with Velcro ties ( P = .5). Two accidental decannulations occurred in the twill group compared to one in the Velcro group ( P = 1.0). Conclusions: Our study demonstrated no differences in skin‐related complications or accidental decannulation between Velcro and twill tracheotomy ties in the immediate postoperative period following tracheotomy. Our study suggests that Velcro ties are a viable alternative to twill ties. Level of Evidence: 1b Laryngoscope, 127:1996–2001, 2017